2024
DOI: 10.1038/s41598-024-54159-w
|View full text |Cite
|
Sign up to set email alerts
|

Principal causes of acute poisoning in an emergency service: experience between 2014 and 2021 at a University Hospital in Southwestern Colombia

David Hurtado,
Jaime A. Quintero,
Yeraldin Alejandra Rodríguez
et al.

Abstract: Acute poisonings are a global public health problem, which implies costs and disease burden for society. In Colombia, there is a significant underreporting of data on acute poisoning and data gaps on the toxicological profile of the population. This study aims to identify the epidemiology of acute poisoning in a high-complexity hospital in southwestern Colombia. A descriptive study with retrospective data collection was performed. The variables were expressed through the measure of central tendency and dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It has been reported that in Kenya, the majority of the cases of acute poisoning among healthcare workers were caused by Dimethoate and Lambda Cyhalothrin (Marete et al 2021). Studies conducted in India have suggested that organophosphates are the primary cause of most Acute Pesticide Poisoning (APP) cases, followed by Pyrethroids (Samaria et al 2024;Hurtado et al 2024). Lambda Cyhalothrin is responsible for most poisoning cases in Asia, Africa, and Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in Kenya, the majority of the cases of acute poisoning among healthcare workers were caused by Dimethoate and Lambda Cyhalothrin (Marete et al 2021). Studies conducted in India have suggested that organophosphates are the primary cause of most Acute Pesticide Poisoning (APP) cases, followed by Pyrethroids (Samaria et al 2024;Hurtado et al 2024). Lambda Cyhalothrin is responsible for most poisoning cases in Asia, Africa, and Latin America.…”
Section: Discussionmentioning
confidence: 99%